On Second-Order Differential Equations with Nonhomogeneous Φ-Laplacian. (2010) - Cecchi Cecchi, Mariella Mariella; Došlá Došlá, Zuzana Zuzana; Marini Marini, Mauro Mauro
Abstract : Equation with general nonhomogeneous Φ -Laplacian, including classical and singular Φ -Laplacian, is investigated. Necessary and sufficient conditions for the existence of nonoscillatory solutions satisfying certain asymptotic boundary conditions are given and discrepancies between the general and classical Φ are illustrated as well.